Answer.AI
Question
Mathematics
( m 3 m 3 n 4 ) 3 (m^(3)*-m^(3)n^(4))^(3)
See Answers
Get the Answer.AI App
Solve problem with AI
Best Answer
Answer: m 9 n 12 . -m^(9)n^(12).
Solution:
We are given the expression ( m 3 m 3 n 4 ) 3 . (m^(3)*-m^(3)n^(4))^(3). We can simplify the expression within the parenthesis first by using the distributive property:
m 3 m 3 n 4 = m 3 n 4 . m^(3)*-m^(3)n^(4)=-m^(3)n^(4).
Now we can substitute this expression in our given expression as follows:
( m 3 m 3 n 4 ) 3 = ( m 3 n 4 ) 3 = ( 1 ) 3 m 3 3 n 4 3 = m 9 n 12 (m^(3)*-m^(3)n^(4))^(3)=(-m^(3)n^(4))^(3)=(-1)^(3)*m^(3*3)*n^(4*3)=-m^(9)n^(12)
Therefore,
( m 3 m 3 n 4 ) 3 = m 9 n 12 . (m^(3)*-m^(3)n^(4))^(3)=-m^(9)n^(12).
You might be interested in...
Explore more...
Get the Answer.AI App
Solve problem with AI